Arthroscopic Repair of Talar Osteochondral Defects With Umbilical Cord Allograft: A Prospective, Single-Center, Pilot Study. Issue 3 (June 2021) - Penner, Murray; Younger, Alastair; Wing, Kevin; Cresswell, Mark; Veljkovic, Andrea
Cryopreserved umbilical cord (UC) allografts have been shown to promote postoperative wound healing by suppressing inflammation and reducing scar formation. The purpose of this study was to determine whether adjunctive use of UC may improve clinical and functional outcomes following arthroscopic repair of talar osteochondral defects (OCDs). A total of 10 patients with talar OCDs that failed nonoperative treatment were enrolled in this single-center, prospective, pilot study. Clinical and functional outcomes were assessed using the Ankle Osteoarthritis Scale (AOS), Foot and Ankle Ability Measure, and Visual Analog Scale (VAS) pain scale at 6, 12, 24, and 52 weeks postoperatively. Results showed a consistent improvement in all outcome measures. VAS pain scores significantly improved from 4.2 ± 2.9 to 1.3 ± 2.2 at 52 weeks (P = .015). AOS difficulty and pain scores nonsignificantly improved from 27.0 ± 24.6 and 33.1 ± 28.3 at baseline to 15.3 ± 20.5 and 14.8 ± 18.7 at 52 weeks, respectively. The clinical outcome improvement was accompanied by significant reduction in OCD defect size and associated bone marrow lesion. This pilot study suggests that adjunctive use of UC during arthroscopic repair of talar OCD may lead to clinical and functional improvement. Levels of Evidence: Level II: Prospective Cohort Study